2014
DOI: 10.1016/j.electacta.2014.08.052
|View full text |Cite
|
Sign up to set email alerts
|

The development of a novel urea sensor using polypyrrole

Abstract: a b s t r a c tThe urease enzyme (Urs) was successfully incorporated into a polypyrrole film (PPy) in one simple electropolymerisation step. The films were formed using different dopant anions. The polypyrrole-urease-chloride film (PPy-Urs-Cl) was deposited from a simple chloride dopant, and the polypyrrole-urease-sulfonated-␤-cyclodextrin (PPy-Urs-SCD) was formed using a sulfonated-␤-cyclodextrin (SCD) dopant. The presence of the Urs within the polymer film was evident from the fibrous morphology, observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Polypyrrole has been doped with anionic CDs to give conducting polymer matrices that exhibit cation exchange properties as the large cyclodextrin is immobile and is not lost on reduction of the polymer [21,22]. These CD-doped polypyrrole films have been used in the electrochemical detection of dopamine [23] and urea [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Polypyrrole has been doped with anionic CDs to give conducting polymer matrices that exhibit cation exchange properties as the large cyclodextrin is immobile and is not lost on reduction of the polymer [21,22]. These CD-doped polypyrrole films have been used in the electrochemical detection of dopamine [23] and urea [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to monitor the level of urea to determine the health of the livers and kidneys in the human body. In the past years, some analytical methods have been developed for urea detection, such as enzymatic assay (Hamilton and Breslin, 2014;Yang and Zhang, 2013;Siqueira et al, 2014;Lin et al, 2013), gas chromatography (Kessler and Siekmann, 1999), calorimetry (Francis et al, 2002), high-performance liquid chromatography , fluorimetry (Roch-Ramel, 1967), surface plasmon resonance (Verma and Gupta, 2014) and electrochemistry (Mondal and Sangaranarayanan, 2013;Srivastava et al, 2012). Despite many advances in urea detection, many of these methods still do not meet the growing demand for more sensitive and selective detection of urea.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Polypyrrole (PPy), as one of the most promising CPs because of its ease of synthesis, good redox properties, high conductivity and excellent environmental stability, 10 has wider potential applications in sensors and electric devices. [11][12][13][14][15] Metallic nanoparticles (MNPs), such as gold nanoparticles (AuNPs), due to their unique structure and fascinating properties such as high e®ective surface area, strong adsorption ability, good biocompatibility and conductivity, have been extensively used to fabricate di®erent kinds of sensors. [16][17][18][19][20][21] It was found that the conductivity and sensing behavior of CPs could be further improved by embedding MNPs into polymer matrix to form a CP-MNP composite.…”
Section: Introductionmentioning
confidence: 99%